The Effect of Ball Milling Time on the Isolation of Lignin in the Cell Wall of Different Biomass - Yang, Guangrong; An, Xueying; Yang, Shilong (Frontiers in Bioengineering and Biotechnology, 2021)
Ball milling technology is the classical technology to isolate representative lignin in the cell wall of biomass for further investigation. In this work, different ball milling time was carried out on hardwood (poplar sawdust), softwood (larch sawdust), and gramineous material (bamboo residues) to understand the optimum condition to isolate the representative milled wood lignin (MWL) in these different biomass species. Results showed that prolonging ball milling time from 3 h to 7 h obviously increased the isolation yields of MWL in bamboo residues (from 39.2% to 53.9%) and poplar sawdust (from 15.5% to 35.6%), while only a slight increasement was found for the MWL yield of larch sawdust (from 23.4% to 25.8%). Importantly, the lignin substructure of β-O-4 in the MWL samples from different biomasses can be severer degraded with the increasing ball milling time, resulting the prepared MWL with lower molecular weight and higher content of hydroxyl groups. Based on the isolation yield and structure features, milling time with 3 h and 7 h were sufficient to isolate the representative lignin in the cell wall of bamboo residues and poplar sawdust, respectively. While, more than 7 h should be carried out to isolate the representative lignin in larch sawdust.